2020
DOI: 10.3390/ijms21176253
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Lipocalin-2 Diminishes Stroke-Reperfusion Injury

Abstract: Oxidative stress is a key contributor to the pathogenesis of stroke-reperfusion injury. Neuroinflammatory peptides released after ischemic stroke mediate reperfusion injury. Previous studies, including ours, have shown that lipocalin-2 (LCN2) is secreted in response to cerebral ischemia to promote reperfusion injury. Genetic deletion of LCN2 significantly reduces brain injury after stroke, suggesting that LCN2 is a mediator of reperfusion injury and a potential therapeutic target. Immunotherapy has the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…In cervical cancer cells, treatment with LCN2-neutralizing antibody reduced the migration and invasion of cells that overexpressed LCN2 [54]. In other diseases, use of an anti-LCN2 neutralizing antibody showed reductions in reperfusion injury after stroke and attenuated skin lesions in a psoriasis mouse model [55,56]. These findings suggest that LCN2 could be an exploitable therapeutic target in IBC and other aggressive tumors.…”
Section: Discussionmentioning
confidence: 89%
“…In cervical cancer cells, treatment with LCN2-neutralizing antibody reduced the migration and invasion of cells that overexpressed LCN2 [54]. In other diseases, use of an anti-LCN2 neutralizing antibody showed reductions in reperfusion injury after stroke and attenuated skin lesions in a psoriasis mouse model [55,56]. These findings suggest that LCN2 could be an exploitable therapeutic target in IBC and other aggressive tumors.…”
Section: Discussionmentioning
confidence: 89%
“…In response to a variety of brain injuries, LCN2 protein is secreted extracellularly, where it can be pharmacologically targeted by therapeutic antibodies and inhibitors. 32,33 Developing neutralizing antibodies to reduce LCN2 neurotoxicity 33 and small-molecule inhibitors to block the expression and secretion of LCN2 35 or interfere with the interaction between LCN2 and its receptors 19 are potential therapeutic strategies. 32 Considering that LCN2 is not expressed in the brain under normal conditions, one of the potential advantages of using LCN2 inhibitors in cell replacement therapy is the minimization of adverse side effects.…”
Section: Discussionmentioning
confidence: 99%
“…LCN2 has been implicated in recruiting resident microglia and peripheral immune cells after brain injury. 23,32,33 To assess the infiltration of microglia and immune cells after transplantation, ipsilateral hemispheres of LCN2 +/+ and LCN2 −/− mice were isolated on days 1 and 7 after transplantation and analyzed by flow cytometry (Figure S4). The percentage of CD45 int CD11b+ microglia was significantly attenuated 7 days after transplantation in LCN2 −/− mice F I G U R E 3 Spatial relationship between LCN2 expression, astrocytes, and microglia surrounding the graft.…”
Section: Recruitment Of Microglia Neutrophils and Monocytes After Transplantation Was Reduced In Lcn2 Deficiency Micementioning
confidence: 99%
“…Supplementing high-density lipoproteins or alpha-1 antitrypsin (an elastase inhibitor) inhibited neutrophil degranulation and the proteolysis of ECM (224). The diminishment of LCN-2 by antibodies significantly reduced brain edema, BBB permeability, and functional outcome after stroke injury (65). Inhibition of MPO by N-acetyl lysyltyrosylcysteine amide significantly decreases IgG extravasation and neurological severity score in stroke (213).…”
Section: Immunotherapies Targeting Bbb Disruption During Ischemic Stroke Therapies Targeting Neutrophilsmentioning
confidence: 99%
“…LCN-2 exacerbateed Evans blue (EB) extravasation and brain edema by reducing the expression of junction proteins, namely claudin-5 and β-catenin, during AIS. Therefore, LCN-2 neutralization can attenuate BBB disruption ( 65 ). However, another study found that LCN-1 reversed the decreased endothelial translocation of ZO-1 and VE-cadherin from the membrane to the cytoplasm of ECs after tumor necrosis factor-alpha (TNF-α) treatment, which mitigated BBB disruption ( 66 ).…”
Section: Role Of Peripheral Immune Cells In the Disruption Of Bbb In Strokementioning
confidence: 99%